حوكمة الشركات كآلية لتحسين الأداء في المؤسسات الصغيرة والمتوسطة دراسة حالة مديرية توزيع الكهرباء والغاز – سوق اهراس - رانية عيادي (My University, 2021)
Interest in the concept of corporate governance has grown in many developed and developing economies alike, especially in the wake of the economic crises that occurred in many countries in Asia, Latin America and Russia in the 1990s, which called for the need to pay attention to the mechanisms and principles of applying corporate governance. This study aimed to shed light on the role of principles and mechanisms of governance in improving the performance of small and medium enterprises, by presenting all theoretical concepts related to corporate governance, in addition to studying a number of principles and mechanisms of governance that improve the efficiency and performance of institutions, and we have conducted a field study In the Directorate of Electricity and Gas Distribution - Souk Ahras - which showed that there is a correlation between the principles and mechanisms of governance and performance. .................................................... تعاظم الاهتمام بمفهوم حوكمة الشركات في العديد من الاقتصاديات المتقدمة والنامية على حد سواء لاسيما في أعقاب الأزمات الاقتصادية التي شهدتها العديد من العديد من دول آسيا وأمريكا اللاتينية وروسيا في عقد التسعينيات الأمر الذي دعا إلى ضرورة الاهتمام بآليات ومبادئ تطبيق حوكمة الشركات. هدفت هذه الدراسة إلى تسليط الضوء حول دور مبادئ و آليات الحوكمة في تحسين أداء المؤسسات الصغيرة والمتوسطة وذلك من خلال عرض جميع المفاهيم النظرية المتعلقة بحوكمة الشركات، بالإضافة إلى دراسة جملة من مبادئ و آليات الحوكمة التي تعمل على تحسين كفاءة وأداء المؤسسات، وقد قمنا بدراسة ميدانية في مديرية توزيع الكهرباء والغاز – سوق اهراس - والتي أظهرت أن هناك علاقة ارتباط بين مبادئ و آليات الحوكمة والأداء